An Analysis of Asatidz’ Instructional Strategies for Improving the Quality of Qur’anic Reading through the An-Nahdliyyah Method at the RTQ of Darul ‘Ulum Islamic Boarding School - Febry Ilham Nur Cholis; Ikhwan Aziz Q; Zainal Arifin; Suhono Suhono (International Journal on Advanced Science, Education, and Religion, 2026)
Islamic boarding schools (pesantren) play a significant role in developing students’ religious competencies, particularly their ability to read the Qur’an. Proficiency in Qur’anic recitation serves as a fundamental basis for understanding Islamic teachings and fostering students’ religious character. Achieving this competence requires well-planned, systematic, and sustainable instructional strategies. This study was conducted at the RTQ of Darul ‘Ulum Islamic Boarding School in Seputih Banyak, Central Lampung, an institution dedicated to improving students’ Qur’anic reading skills. The study employed a qualitative descriptive approach using field research methods. Data were collected through observation, interviews, and documentation, while data validity was ensured through source and technique triangulation. The findings revealed that the teachers (asatidz) implemented instructional strategies encompassing the organization, delivery, and management of Qur’anic reading instruction. These strategies included systematically structured learning materials, a combination of classical and individual teaching methods with direct corrective feedback, the creation of a conducive learning environment, and collaboration with students’ parents or guardians. The implementation of these strategies contributed to improvements in students’ reading fluency, accuracy of makhraj (pronunciation), understanding of tajwid rules, as well as their discipline and self-confidence. Therefore, the instructional strategies implemented at the RTQ of Darul ‘Ulum Islamic Boarding School have proven effective in enhancing students’ Qur’anic reading abilities.